2016
DOI: 10.7860/jcdr/2016/19300.8439
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices (Kap) Relating to Dietary Supplements Among Health Sciences and Non-Health Sciences Students in One of The Universities of United Arab Emirates (UAE)

Abstract: There is a relatively high prevalence of DS consumption among students, which they reported as using to maintain good health and ensure adequate nutrition. However, findings suggest that there are significant differences in the knowledge of health sciences and non-health sciences students pertaining to the health benefits and safety of these supplements. Therefore, awareness of DS usage and information should be integrated into everyday practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
57
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 17 publications
13
57
1
1
Order By: Relevance
“…However, Pelletier & Kendall (1997), on the contrary, argued that individuals with unhealthy nutritional attitudes and behaviors tend to use diet supplements to regulate dietary patterns. In parallel with this study, Alhomoud et al (2016) was found that the frequency of using dietary supplements is higher for teachers whose higher knowledge score about nutrition.…”
Section: Results Conclusion and Recommendationssupporting
confidence: 73%
See 2 more Smart Citations
“…However, Pelletier & Kendall (1997), on the contrary, argued that individuals with unhealthy nutritional attitudes and behaviors tend to use diet supplements to regulate dietary patterns. In parallel with this study, Alhomoud et al (2016) was found that the frequency of using dietary supplements is higher for teachers whose higher knowledge score about nutrition.…”
Section: Results Conclusion and Recommendationssupporting
confidence: 73%
“…According to NHANES-III study, the rate of using at least one dietary supplement was 53.0% (Gahche et al, 2011). Dietary supplements are widely used because they are easily accessible and have beneficial effects on health (Alhomoud et al, 2016). In this study, the frequency of use of diet supplements by teachers was 41.1%.…”
Section: Results Conclusion and Recommendationsmentioning
confidence: 86%
See 1 more Smart Citation
“…Likewise, in Kuwait, health sciences students had suboptimal diet [ 9 ]; and, in Lebanon, the prevalence of overweight/obese students was 32.2%, and their dietary consumption was below the recommended guidelines [ 10 ]. In Iran, most students needed to improve their diet (only 28.5% had a good diet) [ 11 ]; and, in the United Arab Emirates, students had a high prevalence of consumption of dietary supplements [ 12 ]. Low rates of healthy nutrition are evident among university students across the Eastern Mediterranean Region (EMR).…”
Section: Introductionmentioning
confidence: 99%
“…This form is adapted from previous conducted forms 7,8 . Both paper and online surveys were prepared, and students were asked to respond on the spot.…”
Section: Methodsmentioning
confidence: 99%